2 6 4 1 9 2 0
If the last two digits of the number above are m n . enter the answer as m × n − 1 0 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let N = 2 6 4 1 9 2 0 . We need to find N m o d 1 0 0 . Using Chinese remainder theorem on factors 4 and 25, we have:
Factor 4: N ≡ 2 6 4 1 9 2 0 ≡ 0 (mod 4)
Factor 25: N ≡ 2 6 4 1 9 2 0 ≡ ( 2 5 + 1 ) 4 1 9 2 0 ≡ 1 (mod 25) , ⟹ N ≡ 2 5 n + 1 , where n is an integer. Then 2 5 n + 1 ≡ 0 (mod 4) , ⟹ n ≡ 3 and N ≡ 3 × 2 5 + 1 ≡ 7 6 (mod 100) . Therefore, m n − 1 0 = 3 2 .
We want 2 6 4 1 9 2 0 ( m o d 1 0 0 ) .
Write n = 4 1 9 2 0 .
We have 2 6 n ≡ 1 ( m o d 2 5 ) and 2 6 n ≡ 0 ( m o d 4 ) . By the Chinese Remainder Theorem, these two congruences have a unique solution modulo 1 0 0 ; by inspection this is 7 6 , so these are the last two digits we need. The answer is then 7 × 6 − 1 0 = 3 2 .
3 2 , the young age at which Ramanujan died :'(
Since 2 6 2 ⇒ 6 7 6 , and 2 6 3 = 1 7 5 7 6 , the last two digits are 76. Therefore 7 × 6 − 1 0 ⇒ 3 2 .
Problem Loading...
Note Loading...
Set Loading...
2 6 4 1 9 2 0 ( 5 0 − 2 4 ) 4 1 9 2 0 ( m o d 1 0 0 ) 2 4 n ( m o d 1 0 0 ) ⟹ 2 4 4 1 9 2 0 ( m o d 1 0 0 ) m n m × n − 1 0 = ( 5 0 − 2 4 ) 4 1 9 2 0 ≡ 2 4 4 1 9 2 0 ( m o d 1 0 0 ) ≡ { 7 6 : if n is even 2 4 : if n is odd ≡ 7 6 = 7 6 = 7 × 6 − 1 0 = 3 2